The 2nd Alpine Winter Conference on Medicinal and Synthetic Chemistry. (10th June 2021) - Ciulli, Alessio; Hamann, Lawrence; Jahnke, Wolfgang; Kalgutkar, Amit S.; Magauer, Thomas; Ritter, Tobias; Steadman, Vicky; Williams, Scott D.; Winter, Georg; Hoegenauer, Klemens; Krawinkler, Karl Heinz; Stepan, Antonia F.
Abstract: The second biannual Alpine Winter Conference on Medicinal and Synthetic Chemistry (short: Alpine Winter Conference) took place January 19–23, 2020, in St. Anton in western Austria. There were roughly 180 attendees from around the globe, making this mid‐sized conference particularly conducive to networking and exchanging ideas over the course of four and a half days. This report summarizes the key events and presentations given by researchers working in both industry and academia. Abstract : Bright sun and bright ideas : If building your scientific network while breathing cool, crisp mountain air sounds appealing, then this conference series is for you. Here is a summary of the events and presentations that took place at the second biannual Winter Conference on Medicinal and Synthetic Chemistry over the course of four and a half days in January 2020, in the western Tyrolean alps of St. Anton, Austria.